MARKET SURVIVAL CONDITIONS UNDER CONSTANT MARKETING MOBILITY - Stošić Mihajlović, Ljiljana; Trajković, Svetlana (Journal of process management and new technologies, 2019)
In modern conditions, many universities and colleges in the world provide study programs in the field of communications and relations with the target market public. This is because the marketing profession is reputable and provides opportunities for rapid advancement and the pursuit of ambitions that are characteristic of the human race. People doing market research and marketing are optimistic, cheerful, curious, courteous and dedicated people who literally enjoy their jobs. Related to this is their positive attitude towards the media, which stems from their desire to be aware of everything that is happening in the organizations of the world of work, and beyond, in all areas of human activity. This paper is about the conditions of survival in the modern market, with the realization of sustainable competitive advantage, which imply the constant vigilance of the marketing sector.